Renewable sources of energy in Poland – biogas - Babula, Mateusz (Journal of Education, Health and Sport, 2018)
The main cause for the global environmental pollution is obtainment of energy from the conventional sources, that is black and brown coal, mineral oil, natural gas, which when burned, all cause the emission of the greenhouse gases and dusts to the atmosphere and the accumulation of huge amounts of the industrial waste. The intense exploitation of conventional sources of energy on one hand leads to diminishing of those sources at accelerated rate, on the other hand poses as a threat to the environment. One of the proper solutions to this issue is implementing biogas as a source of energy in the production of energy in cogeneration, as well as its introduction to the transport as a renewable fuel in case of refined biogas (bio methane). The increase in renewable energy usage is important mostly due to the possibility of increased independence from imported energy, diversification of delivery sources, as well as creation of conditions to further develop distributed power generation built on locally available resources. Renewable energy in Poland has a particular significance for realization of energy politics of our country. The article characterized the development of biogas production and its usage in the countries of EU and in Poland. The usage of biogas for energetic and transportation purposes had been discussed.